Population Parameters, Feeding And Reproductive Biology Of Rasbora Spp. From The Streams Of Muda Reservoir, Kedah, Malaysia - Mohd Noor, Nurul Shafikah (2020)
A study on the biological aspects of the Rasbora spp. was carried out in five chosen streams of Muda Reservoir for duration of 12 months from November 2014 until October 2015. This study includes the determination of water quality parameters and fish composition, length-weight relationship, relative condition factor, population parameters and feeding biology of R. dusonensis and R. vulgaris, and reproductive biology of R. dusonensis.